2016
DOI: 10.1177/1012690216680602
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the convergence of markets in online sports betting

Abstract: Betting on sports via online platforms has rapidly become a popular form of gambling in many countries. Despite the growing body of research investigating the psychosocial and individual psychological factors determining gambling behaviour, much less attention has been devoted to understanding the market characteristics of online sports betting and its intersection with products from adjacent industries. From an economic convergence perspective, the present paper explores the integration of online sports betti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…- Table 1 about here. -This process is not limited to games and gambling, but is part of a wider trend of media convergence (Jenkins, 2006), and has been studied in reference to other, more established, gambling activities such as sports betting (Lopez-Gonzalez and Griffiths, 2016). The blurring of 3 boundaries between video games and gambling activities has led to a range of problems regarding regulation and legislative issues (Teichert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…- Table 1 about here. -This process is not limited to games and gambling, but is part of a wider trend of media convergence (Jenkins, 2006), and has been studied in reference to other, more established, gambling activities such as sports betting (Lopez-Gonzalez and Griffiths, 2016). The blurring of 3 boundaries between video games and gambling activities has led to a range of problems regarding regulation and legislative issues (Teichert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The blurring of 3 boundaries between video games and gambling activities has led to a range of problems regarding regulation and legislative issues (Teichert et al, 2017). Although the consequences of this trend are yet to be fully assessed, current concerns include the targeting of vulnerable populations through gambling-like experiences, and increased penetration of gambling using socially-accepted vehicles such as sports and video games (Lopez-Gonzalez and Griffiths, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Esports also have a large following via online streaming platforms such as Twitch and YouTube. Furthermore, such activities can be played via a Local Area Network (LAN) connection between computer devices, the events are hosted by sponsors, and have esport play-by-play commentaries, jumbotrons (i.e., large televised screens), sizeable live audiences, and large cash prizes for the best gamers (Adamus 2012;Jenny et al 2016;Jonasson and Thiborg 2010;Lopez-Gonzalez and Griffiths 2016). Taylor (2012) also highlighted in her work, that the rules of esport tournaments, systems, play, judging, and broadcasting can be similar to traditional sports, and professional gamers can be compared to the requirements and practice of the athletes of professional sports (i.e., training, practice, and physical and mental states of athletes).…”
Section: Introductionmentioning
confidence: 99%
“…By turning gambling dynamics into game dynamics, SB can arguably incorporate these characteristics: (i) more engaging and attention-demanding products, with bettors required to perform composite complex actions and calculations; (ii) as bettors adopt a more active role, betting outcomes will be more likely be misconstrued as results of that role; (iii) the positive connotations of playing (e.g., healthy, fun) will help to reduce the associated risks of SB and focus on its entertainment value; and (iv) as bettors become players, the juxtaposition and confusion of roles of those in the field and those betting in their devices could be intensified. The convergence already in motion of gambling and gaming products such as SB, poker, and social games testifies to that effect (Cassidy, 2013;Lopez-Gonzalez & Griffiths, 2016b). Interestingly, a study examining fantasy sports -arguably a seminal form of gamified SB -found that players that were allowed higher levels of customisation in the platform, reported higher winning expectancy and were more likely to believe that they could control the outcome, even when such customisation had no actual effect on it (Kwak, Lee, & Mahan III, 2013).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…In Australia, for instance, SB advertising in 2012 constituted 2.5% of air time of typical sports broadcasts (Milner, Hing, Vitartas, & Lamont, 2013). In contemporary European soccer, with electronic banners around the field almost exclusively devoted to SB brands and shirt sponsorships (Lopez-Gonzalez & Griffiths, 2016b), the proportion is likely to have grown.…”
mentioning
confidence: 99%